Faktor-Faktor yang Mempengaruhi Kelayakan Bisnis Event Equestrian pada Aragon Merdeka Master 2025 di The Hub Indonesia - Dorojatun Zaidan Latasa Muhammad; Ryna Parlyna; Sabo Hermawan (Indo Publishing, 2026)
This research focuses the analysis on the digital business phenomenon within the post-pandemic sport tourism industry, rather than an operational evaluation of the event. The Aragon Merdeka Master (AMM) 2025 case study at The Hub Indonesia is positioned as an instrumental context to understand the fundamental shift from the service economy to the Experience Economy. Despite recording a record participation of 1,751 entries, this event faced significant operational challenges in the form of competition duration extending until 03:00 WIB. This study aims to analyze how Event Experience Quality, Experiential Value, and Willingness to Pay interact in determining Business Feasibility amidst the dynamics between digital visual demands and animal welfare ethical risks. Using a qualitative approach with a case study method, data were collected through digital footprint observation, archival study, and in-depth interviews, then analyzed using Reflexive Thematic Analysis. The theoretical foundation of the research refers to the frameworks of Experiential Marketing (Schmitt, 1999) and Experience Economy (Pine & Gilmore, 1999). The research results reveal the Phygital Gap phenomenon, where the visual innovation of the night session successfully created a digital image of grandeur that compensates for physical management constraints in the field (P1). A digital consumer behavior anomaly was found where operational friction did not decrease WTP (P2), because participants engaged in a value compensation mechanism by prioritizing social validation over physical comfort (P3). However, it is concluded that this business model has fragile feasibility. Financial profits from capacity intensification (P4) face reputational risk challenges and the potential review of the Social License to Operate due to animal welfare issues (P5). This study suggests a strategic transition from a volume-based business model to a value-based model for long-term sustainability.